Aging in South Asia: challenges and opportunities. (21st June 2018) - Chand, Masud
Abstract : Purpose: The countries that make up South Asia have young but rapidly aging populations. The purpose of this paper is to investigate some of the challenges that this rapid aging creates for societies and organizations in South Asia. It also points out how, properly managed, aging populations can create multiple opportunities for societies and organizations alike. Design/methodology/approach: The paper uses secondary data about the aging situation globally. It pays special attention to the demographic situation in South Asian countries and uses as examples policies dealing with aging populations in other countries that have gone through demographic transitions in the recent past. Findings: Aging populations are bringing about numerous challenges in the region, including rising costs for pensions and healthcare, higher dependency ratios, and changing family dynamics. South Asia will enjoy a one-time demographic dividend. Policy makers and managers need to put the right policies in place to ensure that they take maximum advantage of this opportunity. Research limitations/implications: The study is based on secondary data. It is a perspectives piece and does not provide an in-depth study of the specific issues raised. Practical implications: The study details how organizations can best manage this transition. This includes planning for a multigenerational workforce, providing accommodations for older workers, and fostering mentoring, knowledge transfer, cross-training and mixed-age work teams. Social implications: This study analyzes some of the social issues that arise because of aging populations, such as the challenge of creating pension and healthcare systems, dealing with a rising old age dependency ratio, and dealing with a gradual transition to single-family households. Originality/value: This is one of the first studies that look at the coming demographic transition in South Asia, and details some of the challenges and opportunities that arise both in terms of policies and managerial implications.